Reducing children's social anxiety symptoms: exploring a novel parent-administered cognitive bias modification training intervention. - Lau, J; Pettit, E; Creswell, C (2013)
Social fears and worries in children are common and impairing. Yet, questions have been raised over the efficacy, suitability and accessibility of current frontline treatments. Here, we present data on the effectiveness of a novel parent-administered Cognitive Bias Modification of Interpretations (CBM-I) training tool. CBM-I capitalises on findings demonstrating an association between anxiety symptoms and biased interpretations, the tendency to interpret ambiguous situations negatively. Through CBM-I training, participants are exposed to benign resolutions, and reinforced for selecting these. In adults and adolescents, CBM-I training is effective at reducing symptoms and mood reactivity. In the present study, we developed a novel, child-appropriate form of CBM-I training, by presenting training materials within bedtime stories, read by a parent to the child across three consecutive evenings. Compared to a test-retest control group (n = 17), children receiving CBM-I (n = 19) reported greater endorsement of benign interpretations of ambiguous situations post-training (compared to pre-training). These participants (but not the test-retest control group) also showed a significant reduction in social anxiety symptoms. Pending replication and extensions to a clinical sample, these data may implicate a cost-effective, mechanism-driven and developmentally-appropriate resource for targeting social anxiety problems in children.